Infecções de corrente sanguínea (ICS) causadas por candida spp em um centro de referência em oncologia pediátrica na América Latina: epidemiologia e fatores associados - Silva, Adriana Maria Paixao de Sousa da [UNIFESP] (2018)
Introduction: Invasive Fungal Disease (IFD) is an important cause of morbidity and mortality in hospitalized and immunosuppressed children, with blood stream infection (BSI) by Candida spp being the most prevalent infection. The recognition of patients at risk for candidemia is paramount, since this infection does not have specific clinical signs and symptoms and the delay in diagnosis and therapy has an impact on the prognosis. Aim: To characterize the BSI caused by Candida spp in a reference center for pediatric oncology. Materials and Methods: A retrospective cohort study was carried out through the evaluation of data from medical records of pediatric patients, aged 0 to 18 years old, followedup at the Institute of Pediatric Oncology, São Paulo, Brazil, who presented at least one positive blood culture for Candida spp from January 2004 to December 2016. Results: 90 episodes of candidemia were analyzed, with a median age of 4.5 years (0.117.9), with a predominance of males (57.8% 52/ 90) and solid tumors (54.5% 49/ 90). Among the associated factors to BSI by Candida spp, presence of central venous catheter (CVC) (93.3% 84/ 90), previous use of antibiotic (87.8% 79/ 90) and chemotherapy (72.2% 65/ 90) were most prevalent. The most common Candida species were C. albicans (35.5% 32/ 90), C. parapsilosis (30.0% 27/ 90) and C. tropicalis (16.7% 15/ 90). BSI by C. tropicalis was more associated with previous use of chemotherapy (p=0.007) and neutropenia (p=0.001) when compared to the other species, and less associated with presence of CVC (p=0.006). Polymicrobial infection was more associated with BSI by C. albicans compared to nonalbicans Candida (p=0.031). The majority of patients had fever (87.8% 79/ 90) and patients with C. tropicalis had more skin lesions (p=0.006). The majority used polyenes as the first therapeutic option (68.9% 62/ 90) and in 32/90 episodes (35.5%) antifungal replacement was needed. Therapeutic success was achieved in 57/90 episodes (67.1%), with advanced age (p=0.003) and thrombocytopenia (p=0.032) related to therapeutic failure. Death in 30 days was 24.4% (22/90). Predictive factors for death were advanced age (p=0.007) and being in an ICU (p=0.001). Candidemia by C. parapsilosis was a protective factor for evolution to death when compared to C. albicans (p=0.004). Conclusion: BSI by C. tropicalis was more related to chemotherapy, neutropenia and development of skin lesions when compared to other species. Death rate was significant, with advanced age, thrombocytopenia and being in an ICU associated with a worse prognosis. Infection by C. parapsilosis proved to be a protective factor for evolution to death.